Essentials of marketing - Lamb, Charles 1944-; Hair, Joseph F.; McDaniel, Carl D. (South-Western, Cencage Learning, 2012)
Delivers the best coverage of key marketing topics. This book focuses on examples and applications that ensure students not only understand marketing concepts, but also know how to effectively apply them to real-world practice. It illustrates key marketing concepts and showcases the customer experience